Dolphin tale : the junior novel - Reyes, Gabrielle (New York : Scholastic, 2011)
Sawyer, having found an injured dolphin on the beach, forms a unique bond with the creature while trying to help it heal and return to the ocean.
"Based upon the screenplay written by Karen Janszen and Noam Dromi."
3.8
3-6
Keywords: Dolphins -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Dolphins -- Fiction; Human-animal relationships -- Fiction; Dolphins -- Fiction; Human-animal relationship -- Fiction; Movie novels; Movie novels